Dimensiones de la acción tutorial en la Universidad - Franco, Vicente Hernández (Miscelánea Comillas, 2006)
In this work, taking as reference the experience of the Pontificia Comillas University (Madrid, Spain) we propose a model of action tutorial in the university educational grade, which tries to give answer to the new formative demands that are removed of the establishment of the European Space for Higher Education (ESHE). The basic dimensions of the model are three: university counselling, university tutoring/mentoring and university career guidance. Since the assumption of the model of action tutorial advanced and collecting the general tradition and the different concrete experiences of tutoring and attention personalized carried out in Comillas University, the Tutorial Action Plan (TAP) are proposed as main strategy for the establishment generalized of the model in the feature study programs. The TAP is an institutional plan that develops the objectives, contents and organization of the tutorial activities in a specific faculty or concrete qualification. Finally, the establishment of a TAP supposes the institutionalization of the corresponding organizing structures of coordination and its evaluation and continuous improvement.